2021
DOI: 10.4062/biomolther.2020.175
|View full text |Cite
|
Sign up to set email alerts
|

Late Passage Cultivation Induces Aged Astrocyte Phenotypes in Rat Primary Cultured Cells

Abstract: Astrocytes play various important roles such as maintaining brain homeostasis, supporting neurons, and secreting inflammatory mediators to protect the brain cells. In aged subjects, astrocytes show diversely changed phenotypes and dysfunctions. But, the study of aged astrocytes or astrocytes from aged subjects is not yet sufficient to provide a comprehensive understanding of their important processes in the regulation of brain function. In this study, we induced an in vitro aged astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
1
13
1
Order By: Relevance
“…Senescent astrocytes in our study also found these similar changes of indicators. What's more is that the mitochondrial function of senescent astrocytes may decline with increased passaging [24], especially the level of proton leak and ATP, but we found that increased passaging did not affect the level of ATP, which is different from the research before, speculating that this discrepancy may be caused by the difference of length of culturing time and selfregulation of astrocyte itself, but ATP level of the model of oxidative stress of astrocyte indeed changed.…”
Section: Discussioncontrasting
confidence: 92%
“…Senescent astrocytes in our study also found these similar changes of indicators. What's more is that the mitochondrial function of senescent astrocytes may decline with increased passaging [24], especially the level of proton leak and ATP, but we found that increased passaging did not affect the level of ATP, which is different from the research before, speculating that this discrepancy may be caused by the difference of length of culturing time and selfregulation of astrocyte itself, but ATP level of the model of oxidative stress of astrocyte indeed changed.…”
Section: Discussioncontrasting
confidence: 92%
“…CEC treated with PDS showed higher γH2AX fluorescence intensity compared with control cells (Figures 3A,B). We also observed that CEC treated with PDS showed a significant increase in their nuclear size, which is also a feature of cell senescence (Rey et al, 2017;Bang et al, 2021) (Figure 3C). Another cohort of cultured primary CEC was treated either with PDS, or with a vehicle, and stained for SA-β-galactosidase.…”
Section: G4 Stabilization Induces Senescence In Cultured Cecmentioning
confidence: 58%
“…Previous studies have demonstrated that senescent astrocytes have substantially reduced functional capacity compared to their normal counterparts. For example, senescent astrocytes exhibited impaired would healing ability, phagocytic uptake, metabolic function, and neuroprotective capacity (Bang et al, 2021; Pertusa et al, 2007). Among their numerous functions in the adult brain, astrocytes are required for BBB maintenance (Heithoff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%